Themes within lecturers' views on the teaching of linear algebra - Rensaa, Ragnhild Johanne; Hogstad, Ninni Marie; Monaghan, John (International journal of mathematical education in science and technology, 2021)
This paper reports on themes that arose in an investigation of university lecturers' views on the teaching of linear algebra. This focus on themes was the initial part of a study concentrating on four areas: What is important to teach in a first course in linear algebra? Are there teaching methods which are particularly suited for such a course? Are there tools that should/should not be used; and do the answers to these questions vary according to the degree (Engineering or Mathematics) the students follow? Questionnaire data was coded using thematic analysis which generated 11 themes related to the four questions above. The Results section presents the themes. The Discussion section considers the themes as a whole; splits - dualities - in teaching linear algebra; students' challenges with abstraction; aspects of doing mathematics; and pedagogical issues.